Molecular detection of acute hepatopancreatic necrosis disease (AHPND) in Penaeus vannamei shrimps in Costa Rica - Dolz, Gaby (2020)
Proyecto FIDA7 Situación sanitaria del camarón blanco (Litopenaeus vannamei) en zonas productivas de Costa Rica